Frequency of Absolute and Functional Iron Deficiency Anemia in Non-Dialysis Dependent Chronic Kidney Disease Patients - Shahid, Zarwa; Rehman, Misbah; Ahmad, Yahya Azeem; Jamil, Muhammad Irfan; Shahzad, Anjum; Abbas, Ghulam (Indus Journal of Bioscience Research, 2025)
Background and Aim: Iron deficiency is a common and clinically significant complication in non-dialysis dependent chronic kidney disease (CKD) patients, manifesting as either absolute or functional iron deficiency. This study aimed to assess the frequency and distribution of these subtypes of iron deficiency anemia (IDA) across different CKD stages and to identify their independent predictors. Materials and Methods: A cross-sectional study was conducted at the Nephrology Outpatient Department of Nishtar Hospital, Multan over a period of 6 months from July 2024 to December 2024, enrolling 451 adult patients with CKD stages 3a to 5 (non-dialysis dependent). Hemoglobin, serum ferritin, transferrin saturation, and serum iron were evaluated to classify iron deficiency. Results: Anemia was observed in 346 patients (76.7%). Of these, 133 (29.5%) had absolute iron deficiency (AID), and 213 (47.2%) had functional iron deficiency (FID). Anemia prevalence increased significantly with advancing CKD stage (p = 0.002). AID was highest in stage 5 (49.1%), while FID peaked in stage 4 (58.2%) (p < 0.05 for both). Hemoglobin was significantly lower in AID (9.2 ± 1.1 g/dL) and FID (9.7 ± 1.3 g/dL) groups versus non-anemic patients (12.9 ± 0.8 g/dL; p < 0.001). Serum ferritin was lowest in AID (51.2 ± 15.7 ng/mL) and highest in FID (173.6 ± 42.5 ng/mL). Transferrin saturation and serum iron levels were significantly reduced in both deficiency groups (p < 0.001). Multivariate analysis revealed age <60 years (aOR: 1.79; p = 0.027) and CKD stage 5 (aOR: 2.23; p = 0.024) as independent predictors of AID, while CKD stage 4 was significantly associated with FID (aOR: 2.93; p < 0.001). Conclusion: Anemia, particularly functional iron deficiency, is prevalent in non-dialysis dependent CKD patients. Disease stage and age significantly influence the type of iron deficiency, highlighting the need for stage-specific evaluation and management.